Bilateral Implantation of Shear Stress Modifier in ApoE Knockout Mouse Induces Cognitive Impairment and Tau Abnormalities - Nie, Shuke; Tan, Yang; Zhang, Zhentao; Chen, Guiqin; Xiong, Jing; Hu, Dan; Ye, Keqiang; Zhang, Yunjian; Cao, Xuebing; Chen, Liam; Zhang, Zhaohui (Frontiers in Aging Neuroscience, 2018)
Vascular cognitive impairment encompasses all causes of cerebrovascular disease that lead to cognitive decline, or overt dementia, atherosclerotic disease being the most common contributor. However, few rodent models that mimic the pathology of vascular cognitive impairment replicated the clinical cerebrovascular atherosclerosis. Here we aimed to investigate the mechanism underlying vascular cognitive impairment in an ApoE knockout mouse model fed with western style food with implantation of bilateral shear stress modifiers. We established a cognitive decline in spatial learning and memory developed in the bilateral modifier treated mice. Brain imaging and pathological examinations demonstrated reduced glucose intake and neuronal loss in hippocampus. Although no amyloid plaques or neurofibrillary tangles were observed, tau pathology including hyperphosphorylation, paired helical filament formation and pathologic truncation were found at considerable higher extent in the bilateral modifier group 8 weeks post the procedure. In addition, gliosis and microglia activation were confirmed in corpus callosum and ventral striatum. Thus, this ApoE knockout mouse model faithfully replicates the stenosis of common carotid artery and cognitive impairment following atherosclerotic deposition and global cerebral hypoperfusion. The close correlation of cognitive decline and tau pathology indicates the toxic tau species could be at least partially responsible for the neurodegenerative changes induced by the chronic hypoxia/ischemia.